Isolados bacterianos do besouro-praga Sphenophorus levis: potencial para degradação de poliestireno expandido - Madera, Karen Susana Manjarrez (Universidade Federal de São Carlos, 2022)
The present work aimed to verify the potential of endosymbionts bacterial strains isolated from the intestine of larvae of the insect pest Sphenophorus levis (Coleoptera: Curculionidae) for the degradation of expanded polystyrene (EPS) through the use of bioinformatics tools. The study was based on initial observations of active consumption of EPS by the insect larvae. Initially, S. levis larvae were submitted to intestinal dissection for isolation of the most abundant strains and genomic DNA sequencing in triplicates. The identification of bacterial strains was performed using single copy genes, taxonomic markers, obtaining genomes associated with Microbacterium hominis, Bacillus spp., and Stenotrophomonas maltophila. Phenotypic traits were predicted from the genome sequence with high accuracy, since traits such as morphology and oxygen sensitivity agreed with the biochemical characterization of the strains. Genes related to polystyrene degradation were identified only in the strain Bacillus spp. SLBac4, and with these data we proposed a metabolic pathway for EPS biodegradation. The Bacillus spp. SLBac4 has four enzymes involved in side-chain oxidation and direct disruption of the styrene aromatic ring, however, the initial depolymerization of EPS remains unknown. Within the four enzymes, styrene monooxygenase was characterized and compared for its specificity in the initial step of EPS degradation. In addition, currently, there are no studies on enzymes that directly degrade EPS. Our study provides the first evidence related to a possible metabolic mechanism of enzymatic biodegradation of bacteria from the gut of S. levis larvae, enabling the development of new future strategies for bioremediation of pollutants such as EPS.
Bacterial isolates from the pest beetle Sphenophorus levis: potential for degradation of expanded polystyrene
Keywords: Sphenophorus levis; Microbioma intestinal; Biodegradação; Poliestireno expandido; Estireno monooxigenase; Sphenophorus levis; Intestinal microbiome; Biodegradation; Expanded polystyrene; Styrene monooxygenase; CIENCIAS BIOLOGICAS::BIOQUIMICA::BIOLOGIA MOLECULAR; CIENCIAS BIOLOGICAS::BIOQUIMICA::BIOQUIMICA DOS MICROORGANISMOS